Reducing hospital admissions of healthy children with functional constipation: a quality initiative. Issue 2 (12th October 2017) - Deneau, Mark; Mutyala, Ramakrishna; Sandweiss, David; Harnsberger, Janet; Varier, Raghu; Pohl, John F; Allen, Lauren; Thackeray, Callie; Zobell, Sarah; Maloney, Christopher
Abstract : Functional constipation (FC) is a common medical problem in children, with minimal risk of long-term complications. We determined that a large number of children were being admitted to our children's hospital for FC in which there was no neurological or anatomical cause. Our hospital experienced a patient complication in which a patient died after inpatient treatment of FC. Subsequently, we developed a standardised approach to determine when paediatric patients needed hospitalisation for FC, as well as to develop a regimented outpatient therapeutic approach for such children to prevent hospitalisation. Our quality improvement initiative resulted in a large decrease in the number of children with FC admitted into the hospital as well as a decrease in the number of children needing faecal disimpaction in the operating room. Our quality improvement process can be used to decrease hospitalisations, decrease healthcare costs and improve patient care for paediatric FC.